When Trust Falters: The Impact Of Negative Information On Traditional Medicine Repurchase Intentions In Indonesia - Rizka Zulfikar; Ananda Sabil Hussein; Nanang Suryadi; Margono Margono (International Journal of Science and Environment (IJSE), 2025)
This study investigated how exposure to negative information influenced consumer trust and repurchase intention within Indonesia’s traditional medicine market. By integrating the Theory of Planned Behavior with Trust Deterioration Models, the research addressed a critical gap concerning the impact of adverse digital narratives on culturally embedded health products. A quantitative, cross-sectional design was employed using an online survey that collected 207 valid responses from traditional medicine users across Indonesia. Data were analyzed using Descriptive analysis and Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate both measurement and structural models. Results showed that negative information significantly undermined trust in traditional medicine, which in turn reduced consumers’ intention to repurchase. The strongest effects emerged from the perceived credibility and virality of negative news, which heightened risk perception and skepticism toward product quality, brand integrity, and regulatory oversight. Trust was found to partially mediate the relationship between negative information and repurchase intention, highlighting its central role as both a psychological enabler and a vulnerability point in consumer behavior. These findings provided substantial implications for producers, regulators, and marketers in preserving consumer confidence, suggesting the urgent need for reputation management strategies and transparent communication to counteract digital skepticism in emerging markets.